A novel intragenic marker targeting the ectodomain of bacterial blight-resistance gene Xa21 for marker-assisted selection in rice. Issue 6 (1st November 2020) - Nanayakkara, Dhanesha; Edirisingha, Iresha; Dissanayake, Lakshika; Weerasinghe, Deepika; Suriyagoda, Lalith; Herath, Venura; Perera, Chandrika; Jayatilake, Dimanthi
ABSTRACT: The rice ( Oryza sativa L.) Xa21 gene is known to confer resistance against Xanthomonas oryzae pv. oryzae, the causal organism of bacterial blight (BB) through its involvement in pathogen recognition and immunity responses. The closely linked sequence-tagged site marker pTA248 is frequently used for marker-assisted selection (MAS) of Xa21 . However, lower precision and linkage drag of linked-markers hinders its reliability and effectiveness in MAS compared to flanking/intergenic markers. In the current study, a diagnostic intragenic marker was developed for MAS of Xa21 in rice. The new marker ABUOP0001 targets a 19-bp insertion/deletion on the ectodomain of Xa21 and amplifies a 200-bp amplicon from rice line IRBB 62 (known to carry the "resistance allele"), and a 181-bp amplicon from IRBB 7 (known to carry the "susceptible allele"). The ABUOP0001 marker assay identified the resistance allele in 15 rice lines/accessions. In a field study, 14 of these lines/accessions had highly resistant BB responses, and one had an intermediate response. Further, Xa21 resistance allele was identified in 1, 675 rice accessions through an in-silico genomic sequence analysis. The marker ABUOP0001 performs better than the previously used linked-marker pTA248 (anchored to a gene 225 kbp upstream of Xa21 ) as ABUOP0001 is an intragenic marker targeting the functionally important ectodomain of Xa21 . Further, ABUOP0001 is compatible for high-throughput screening with high-resolution melting and can be multiplexed effectively with an intragenic marker of BB resistance gene Xa4 . Therefore, ABUOP0001 can be recommended as a high-throughput diagnostic intragenic marker for MAS of Xa21 in rice.